Factors Related To The Timeliness Of Re-Injection Of Injectable Birth Control Acceptors 3 Months At Pratama Aulia Medika Clinic, Cirebon Regency - Febrilianti, Ega; Tonasih, Tonasih; Mutya Sari, Vianty; Nurhasanah, Nurhasanah (Jurnal Medisci, 2025)
Background. Family planning is an effort to measure the number and distance of children desired. Injectable contraceptives are a way to prevent pregnancy from occurring through hormonal injections. The failure of the injectable contraceptive method is caused by the delay of the acceptor to re-inject. The rate of inaccuracy in the re-visit of birth control injections at the Aulia Medika Primary Clinic is still high at 52.9%. Purpose. This study aims to determine the factors related to the timeliness of re-injection of injectable birth control acceptors for 3 months at the Aulia Medika Primary Clinic, Cirebon Regency in 2025. Method. This study uses analytical research. Observational research method with a cross sectional approach. The population was 191 acceptors who visited in the January-December 2024 period and a sample of 66 samples. The sampling technique proposes "non probability sampling" with the purposive sampling method. The research instrument used medical records and questionnaire sheets and statistical analysis using Chi-Square test analysis. Results. The results of the relationship between knowledge and the accuracy of the 3-month injectable birth control acceptor revisit with a p value of 0.000 < α (0.05), the relationship between husband support and the accuracy of the 3-month injectable birth control acceptor with a p value of 0.002. Conclusion. The conclusion of this study is that there is a relationship between knowledge and support of husbands and the timeliness of re-injection of injectable birth control acceptors for 3 months at the Aulia Medika Primary Clinic, Cirebon Regency in 2025.